Penerapan Prinsip 5C 7P dalam Upaya Kehati-hatian (Prudential Principle) Risiko Pembiayaan pada BSI KCP Purwoharjo Menurut Perspektif Islam - Rofiq, Ahmad Sahrul; Khoiruddin, Muh.; Rachmawati, Afria (Jurnal Manajemen dan Ilmu Administrasi, 2025)
This study aims to analyze the implementation of the prudential principle in financing distribution at BSI KCP Purwoharjo through the application of the 5C principles (Character, Capacity, Capital, Collateral, Condition of Economy) and 7P principles (Personality, Purpose, Payment, Protection, Prospect, Party, Profitability), viewed from the perspective of Islamic economics. This research employs a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman & Saldana technique. The findings reveal that consistent implementation of the 5C and 7P principles effectively minimizes the risk of problematic financing and strengthens the institution’s credibility. From an Islamic perspective, applying the prudential principle reflects the trust (amanah) and moral responsibility of Islamic financial institutions in managing the public’s funds, aligned with the principles of justice, transparency, and public benefit (maslahah). Therefore, the 5C and 7P principles are not only technical analytical tools but also embody ethical values in the Islamic banking system.